2020
DOI: 10.1111/joor.12936
|View full text |Cite
|
Sign up to set email alerts
|

The effects of sarcopenic dysphagia on the dynamics of swallowing organs observed on videofluoroscopic swallowing studies

Abstract: Objectives:The aim of the present study was (a) to determine the relationship of videofluoroscopic swallowing study (VFSS) findings of the swallowing musculature with the diagnostic criteria for sarcopenic dysphagia and (b) to examine the usefulness of VFSS for diagnosing sarcopenic dysphagia. Methods:The participants were 132 patients (mean age, 80.4 ± 8.8 years). Their skeletal muscle mass, nutritional status and swallowing functions as assessed by VFSS findings were measured. Also, the relationship between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…However, this study found no significant association between these disorders and the recovery of oral intake. Recent studies have reported that pharyngeal clearance is likely to decrease in patients with sarcopenia due to the enlarged pharyngeal cavity, 11 weaker pharyngeal contractility and upper oesophageal sphincter dysfunction 12 . However, we did not take the data of sarcopenia‐related items in this study.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, this study found no significant association between these disorders and the recovery of oral intake. Recent studies have reported that pharyngeal clearance is likely to decrease in patients with sarcopenia due to the enlarged pharyngeal cavity, 11 weaker pharyngeal contractility and upper oesophageal sphincter dysfunction 12 . However, we did not take the data of sarcopenia‐related items in this study.…”
Section: Discussionmentioning
confidence: 95%
“…However, this study found no significant association between these disorders and the recovery of oral intake. Recent studies have reported that pharyngeal clearance is likely to decrease in patients with sarcopenia due to the enlarged pharyngeal cavity, 11 weaker pharyngeal contractility and upper oesophageal sphincter TA B L E 2 Comparison between the oral feeding group and the tube feeding group 12 However, we did not take the data of sarcopenia-related items in this study. Therefore, it is necessary to further investigate the association between sarcopenia and oral intake recovery in patients with aspiration pneumonia in the future.…”
Section: Oba Et Al Reported That the Glasgow Coma Scale And Repetitivementioning
confidence: 95%
“…Previous studies have reported the swallowing characteristics of older adults with sarcopenia. For example, patients with sarcopenic dysphagia had low pharyngeal muscle mass, weaker pharyngeal contractility, and upper esophageal sphincter dysfunction [12, 13]. Although the participants in this study were community-dwelling older women without dysphagia, the similar decline in swallowing function in patients with dysphagia could be due to sarcopenia.…”
Section: Discussionmentioning
confidence: 97%
“…Dysphagia in older adults is a frequent and serious condition that impairs swallowing efficiency and safety with increased risk of diminished nutritional intake and aspiration of foods and liquids [ 1 , 2 ]. Consequently, dysphagia is associated with aspiration pneumonia, malnutrition, weight loss, frequent hospital admissions with prolonged length of stay (LOS), increased mortality, decreased quality of life, as well as increased healthcare costs [ 1 , 3 , 4 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%